2022
DOI: 10.1088/1755-1315/1038/1/012074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Harvest and Postharvest Handling on Quality of Moringa Leaf Powder

Abstract: Moringa Oleifera is a highly nutritious plant with a plethora of uses in various fields of life. It serves as food for humans and animals, soil amendment, water purification, skincare, etc. Almost all parts of the plant are valuable and have potential commercial value. The leaves contain vitamin C in quantities that exceed orange, vitamin A exceeds carrot, calcium exceeding milk, and potassium exceeding banana. Another remarkable property of the plant is it full complement of essential amino acids, anti-bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The leaves were harvested in the morning in around November, after the rainy season. However, they have been reported that to obtain the maximum biological activities of the bioactive compounds, the leaves should be harvested in the early morning [29] and the bioactive contents are highest in February [30]. The voucher herbarium specimen has been deposited in the Forestry Herbarium, Royal Forest Department, Bangkok (BKK-PC-1).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The leaves were harvested in the morning in around November, after the rainy season. However, they have been reported that to obtain the maximum biological activities of the bioactive compounds, the leaves should be harvested in the early morning [29] and the bioactive contents are highest in February [30]. The voucher herbarium specimen has been deposited in the Forestry Herbarium, Royal Forest Department, Bangkok (BKK-PC-1).…”
Section: Plant Materialsmentioning
confidence: 99%